(untitled) (Revista Científica Compendium, 2019)
e public policies (PP) established by the governments of Latin America in the energy supply sector are determining factors in the control of Greenhouse Gas (GHG) emissions. e objective of this research is to determine which PP in the energy supply sector are adopted in Latin America, as well as to link the PP used in the region to the Energetic Indicators of Sustainable Development (EISD). e methodology applied has the following characteristics: the source of data collection is documentary and the studied population is made up of Latin American countries. e results show that the most frequent PP present among the countries are the "increase in the share of renewable energies", "promotion and increase in energetic eﬃciency" and "diversiﬁcation of the energy matrix". Next, the PP were linked to the EISD, which allows an association of both two. is is necessary for the analysis or the determination of eﬃciencies in subsequent investigations. Among the conclusions, most of the countries in Latin America advance to generate "green energy", or at least make attempts to do so, which contributes to the control of GHG emissions from an important sector.